A Proposed Online Platform for Ranking Place Brands Identity Characteristics of Official Tourism Websites - Briciu, Victor-Alexandru; Demeter, Robert; Nechita, Florin; Kavoura, Androniki; Briciu, Arabela (Springer International Publishing, 2019)
This study aims to clarify the ways in which the authorities involved in place brand management choose to use new technologies to communicate their online identity. A descriptive-explanatory research was employed focusing on a methodology repository, applying an instrument for analysis and addressing the online identity of place brands issue. As a quantitative-qualitative alternative, content analysis was chosen for the communication content, while the work technique consisted of frequency analysis applied to a coding grid for the analysis of the data collected. The ICT component involved in this research, a proposed online platform generates an automatic score calculation algorithm for place brands obtained by applying the analysis grid to web sites. This score involved building composite indexes of the analyzed dimensions and placing the brands in a ranking of all the analyzed sites. As more sites are being added, the user can interpret the charts generated by the application. By analyzing ten official websites based on specific criteria which promote brands, we were able to capture various ways in which the authorities involved in the websites’ management understand the use of the Internet in communicating the online identity of brands.
Keywords: place brands; identity characteristics; tourism websites